Caribbean Report 25-01-2000 - The British Broadcasting Corporation; Richards, Ken (anchor); Frazier, Tony (correspondent); Robinson, Arthur (interviewee); Josiah, Austin (interviewee); Nash, Debbie (correspondent); Reynolds, Brian (interviewee); Gordon, Orin (correspondent) (The British Broadcasting Corporation, 2000)
1. Headlines: (00:00-00:27) 2. The Attorney General of Trinidad and Tobago has informed the country’s head of state that he has no say in the removal of appointment of government Senators. One week ago Basdeo Panday advice the President to revoke the appointments of 2 Tobago Senators and appoint 2 others but President Arthur Robinson has responded telling Mr. Panday that removing the 2 Senators have far-reaching consequences for the twin island state of Trinidad and Tobago (00:28-06:12) 3. Mediation talks in Antigua appear to have been successful to hold off the strike threatened by LIAT pilots. They had indicated on Monday that they would have taken industrial action if LIAT failed to meet their salary demands. Antiguan Labour Commissioner Austin Josiah mentioned that mediation has so far reached an agreement on certain key issues. The agreement is that all salaries will be paid on the 31st of January (06:13-08:20) 4. St. Lucia’s Minister of Public Utilities has given a grudging welcome by telephone giant Cable and Wireless to reduce the cost for telephone calls for Dominicans and St. Lucians. The price of calls has been cut by more than half but St. Lucians will have to wait another month for this to take effect (08:21-09:38) 5. A court in the Bahamas has been hearing graphic evidence in the case of a murdered British tourist, Joan Clarke, that has attracted international interest. Giving evidence was the pathologist linked to the case. (09:39-10:56) 6. Caribbean countries are pushing for a UN Initiative to help regulate their own offshore banking services (10:57-13:26) 7. Parties contesting elections in Anguilla have to move up their operations by a week. That is because the Queen’s second son, Andrew is to due to visit British overseas territories the same time (13:27-14:58)